Pendidikan Teman Sebaya melalui Pemberdayaan Kader Posyandu Remaja terhadap Pengetahuan, Sikap, dan Perilaku Remaja tentang Manfaat Gizi dalam Pencegahan Stunting: Penelitian Kuasi Eksperimen - Rasmaniar, Rasmaniar; Nurlaela, Euis; Ahmad, Ahmad; Nurbaya, Nurbaya (Poltekkes Kemenkes Kendari, 2022)
As many as 53% of adolescents have severe energy deficiency and 48% severe protein deficiency. The risk is greater for young women, mothers-to-be, where nutritional deficiencies will have an impact on the health of the mother and baby during pregnancy and childbirth, such as children born with low birth weight who can later become stunted. A youth posyandu service program is needed to prevent stunting problems as early as possible. This study aims to determine the effect of empowering Youth Posyandu Cadres on knowledge of attitudes and behavior of adolescents about nutrition in preventing stunting in Kendari City. This type of research is a quasi-experimental design with a one group pretest-posttest design which was carried out in July-November 2021, carried out on 45 posyandu cadres and 100 youth posyandu participants in the working area of UPTD Puskesmas Puuwatu and UPTD Puskesmas Abeli Kendari City. Before the training most of the youth posyandu cadres were unskilled, after the training most of the posyandu cadres were skilled. The knowledge, attitudes and behavior of cadres at the pretest were mostly lacking, at the post-test most of them became good. Most of the youth participating in the posyandu had less knowledge, attitudes and behavior on the pretest, after peer education the aspects of knowledge, attitudes and behavior of the teenagers were mostly good. Statistically there are significant differences before and after peer training and education on the characteristics of the study. Regular and continuous training is required.